The association between the admission to wards with open- vs. closed-door policy and the use of coercive measures - Krückl, Jana S.; Moeller, Julian; Imfeld, Lukas; Schädelin, Sabine; Hochstrasser, Lisa; Lieb, Roselind; Lang, Undine E.; Huber, Christian G. (Frontiers in Psychiatry, 2023)
Introduction Psychiatric treatment on a ward with open-door policy is associated with reduced numbers of coercive measures. The effect of the door policy of previous stays, however, has not been investigated. Methods The data set consisted of 22,172 stays by adult inpatients in a psychiatric university hospital between 2010 and 2019. Pairs of consecutive stays were built. The outcome variable was the occurrence of coercive measures during the second stay. Results Compared to treatments on wards with a closed-door policy at both stays, treatments on wards with an open-door policy at the second stay had smaller odds for coercive measures (OR ranging between 0.09 and 0.33, p < 0.01). In addition, coercive measures were more frequent in treatment histories where patients previously treated on a closed ward were admitted to a ward with an open-door policy and subsequently transferred to a ward with a closed-door policy at the second stay (OR=2.97, p = 0.046). Discussion Treatment under open-door policy is associated with fewer coercive measures, even in patients with previous experience of closed-door settings. The group of patients who were admitted to a ward with an open-door, then transmitted to a ward with a closed-door policy seem to be prone to experience coercive measures. Clinical strategies to keep these patients in treatment in an open-door setting could further reduce coercive measures.